Enhancing Students’ Learning Independence through Self-Regulated Learning (SRL) Assisted by Wadhwani Ignite Learning Management System (LMS) in Entrepreneurship Courses - Achmad Mustofa; Hendra Koesmara; Awaluddin Awaluddin (Journal of Economics Education and Entrepreneurship, 2026)
This study aims to determine the effect of the implementation of Self-Regulated Learning (SRL) assisted by Wadhwani Ignite Learning Management System (LMS) on increasing student learning independence in entrepreneurship courses at Universitas Syiah Kuala. This study uses a pre-experimental design method with a one-group pretest-posttest design. The research subjects amounted to 118 students who took entrepreneurship courses. Data collection was carried out through a learning independence questionnaire given before and after treatment. The implementation of SRL was carried out for seven meetings by utilizing learning features in Wadhwani Ignite LMS, such as learning materials, discussion forums, assignments, and online quizzes. Data analysis was carried out using a gain test to determine the increase in student learning independence. The results showed that the average pretest score of 64.25 increased to 82.70 in the posttest with an N-Gain value of .52 which was in the medium category. These results show that the application of SRL assisted by Wadhwani Ignite LMS is able to increase students' learning independence, especially in the aspects of learning independence, self-management, disire for learning, and problem-solving skills. Thus, the use of Wadhwani Ignite LMS can be an effective digital learning alternative in supporting students' independent learning in entrepreneurship courses.